Kidney health for all: bridging the gap in kidney health education and literacy - Langham, Robyn; Kalantar-Zadeh, Kalantar; Bonner, Ann; Balducci, Alessandro; Hsiao, Li-Li; Kumaraswami, Latha; Laffin, Paul; Liakopoulos, Vassilios; Saadi, Gamal; Tantisattamo, Ekamol; Ulasi, Ifeoma; Lui, Siu-Fai; et al. (Insight Urology, 2022)
The high burden of kidney disease, global disparities in kidney care, and poor outcomes of kidney failure bring a concomitant growing burden to persons affected, their families, and careers, and the community at large. Health literacy is the degree to which persons and organizations have or equitably enable individuals to have the ability to find, understand, and use information and services to make informed health-related decisions and actions for themselves and others. Rather than viewing health literacy as a patient deficit, improving health literacy largely rests with health care providers communicating and educating effectively in codesigned partnership with those with kidney disease. For kidney policy makers, health literacy provides the imperative to shift organizations to a culture that places the person at the center of health care. The growing capability of and access to technology provides new opportunities to enhance education and awareness of kidney disease for all stakeholders. Advances in telecommunication, including social media platforms, can be leveraged to enhance persons’ and providers’ education; The World Kidney Day declares 2022 as the year of “Kidney Health for All” to promote global teamwork in advancing strategies in bridging the gap in kidney health education and literacy. Kidney organizations should work toward shifting the patient-deficit health literacy narrative to that of being the responsibility of health care providers and health policy makers. By engaging in and supporting kidney health–centered policy making, community health planning, and health literacy approaches for all, the kidney communities strive to prevent kidney diseases and enable living well with kidney disease.